THE EFFECT OF USING EPOXY RESIN VARIATIONS ON THE VALUE OF COMPRESSIVE STRENGTH, SPLIT STRENGTH, AND ELASTIC MODULUS OF POLYMER MORTARS USING RIVER SAND - Novita, Arisia; Elvira, Elvira; Priadi, Eka; Herwani, Herwani (Fakultas Teknik Universitas Tanjungpura, 2024)
The rapid development of physical and infrastructure projects in Indonesia necessitates efficient building materials. Mortar, a standard construction material comprising fine aggregate, water, and cement, has strength, environmental resistance, and flexibility limitations. This study investigates using epoxy resin as a substitute for cement in mortar production. Epoxy resin, a liquid material that hardens into a strong binder, offers potential benefits such as accelerated setting time and increased strength. The research uses river sand as the fine aggregate and varies the epoxy resin content from 5%, 10%, 15%, 20%, and 25% of the material volume. Tests will measure compressive strength, split tensile strength, and modulus of elasticity across different epoxy resin compositions. Results from Tanjung Pura University's Materials and Construction Laboratory in Pontianak indicate that adding epoxy resin significantly improves compressive strength (up to 35.92 MPa at 25% resin) and tensile strength (up to 3.82 MPa at 25% resin). However, adding epoxy resin leads to a decreased modulus of elasticity, indicating increased deformability. This research sheds light on epoxy resin's impact on mortar strength and informs potential applications in concrete repair and construction.